DEVELOPMENT AND FEASIBILITY ASSESSMENT OF A DIGITAL STUNTINGMETER FOR CHILD GROWTH MONITORING IN INDONESIA (Proceedings of the International Conference on Public Health, 2026)
Child malnutrition, including stunting, wasting, and underweight, remains a major public health challenge in Indonesia, with long-term consequences on cognitive development, productivity, and national economic growth. Accurate and real-time growth monitoring is essential for the early detection and timely nutritional interventions. This study presents the development and feasibility assessment of the Digital Stuntingmeter, an ultrasonic-based anthropometric device designed to improve measurement accuracy and enable real-time integration with national health information systems. A multiparameter feasibility study was conducted covering technical, economic, social, and regulatory aspects. Technical feasibility was evaluated through laboratory-based accuracy testing by comparing Digital Stuntingmeter measurements with a gold-standard FLUKE laser distance meter. Social feasibility and user acceptance were assessed among 120 health cadres, midwives, and nutritionists using a structured survey based on the Diffusion of Innovations theory and qualitative Force Field Analysis. Economic feasibility was analyzed through production cost estimation, return on investment (ROI), and break-even point calculations, while regulatory feasibility was assessed against national medical device and child anthropometric standards. The results demonstrated high measurement accuracy, with an average deviation of ±0.2 cm, and strong user acceptance, with a mean acceptance score of 8.62 on a 10-point scale. The device supports both offline and online operation and enables real-time data integration with national systems such as e-PPGBM and SIGIZI. Economically, the estimated unit cost was 365 USD, with a positive ROI and a short break-even period under institutional procurement scenarios. The Digital Stuntingmeter shows strong potential for widespread application through institutional adoption in primary health care settings, particularly Posyandu and Puskesmas. With regulatory alignment and a clear commercialization pathway, this innovation offers a scalable and sustainable solution to strengthen child growth monitoring and support national stunting reduction strategies.
Keywords: stunting; digital anthropometry; child growth monitoring; early detection; feasibility study; health technology